Are you Ready2Help? Conceptualizing the management of online and onsite volunteer convergence. (14th September 2017) - Schmidt, Arjen; Wolbers, Jeroen; Ferguson, Julie; Boersma, Kees
Abstract : Citizens have often been found to converge on disaster sites. Such personal convergence is increasingly supported by online informational convergence. The adoption of online platforms represents an opportunity for response organizations to manage these two different manifestations of citizen convergence. We analyse one such platform, "Ready2Help", developed by the Red Cross in The Netherlands. Our research demonstrates that by utilizing platforms, response organizations are able to transcend the boundaries between different types of organized behaviour during disaster. We extend the original conceptualization of organized behaviour, as previously described by the Disaster Research Center, explaining how the development of new platforms channels convergence of citizens and information. As such, platforms provide an interface between established, expanding, extending, and emergent forms of organized behaviour. These developments change the landscape of organized behaviour in times of disaster.